Accuracy of Maternal Reports of Young Children's Dental Disease Status: Avon Longitudinal Study of Parents and Children - Aderonke A. Akinkugbe; Tegwyn H. Brickhouse; Dipankar Bandyopadhyay; Marcelle M. Nascimento (MDPI AG, 2020)
Background: Parental reports of their children’s health status is integral to pediatric medical and dental care. Therefore, understanding the accuracy of such reports is vital. Our objectives were to (1) assess the correlation between maternal reports of their children’s indicators of caries experience (subjective assessment) and actual caries status determined by oral examination (objective assessment), and (2) identify potential modifiers of this correlation. Methods: Longitudinal data from the Avon longitudinal study of parents and children (n = 1429) was used to assess the correlation between maternal reports of the number of missing and filled teeth of children aged 38 months, 54 months, and 5.5 years and clinical oral examinations of decayed, missing and filled teeth conducted when the same children were 31, 43 months, and five years of age. Homogeneity chi-square tests assessed differences in correlations according to sociodemographic factors. Results: Overall, we found a statistically significant correlation that was weak to moderate in magnitude. Maternal reports of missing teeth at 38 months was significantly correlated with decayed teeth, 0.27 (p < 0.001); missing teeth, 0.23 (p < 0.001), and the decayed, missing and filled (dmft) index, 0.35 (p < 0.001) based on oral examination at 31 months. A maternal report of filled teeth at 54 months was significantly correlated with decayed teeth, 0.30 (p < 0.001); filled teeth 0.30 (p < 0.001), and dmft 0.40 (p < 0.001) at 43 months. Mothers tended to underestimate the extent of missing and filled teeth in their children irrespective of the child’s age, but the extent of underestimation was greater among younger children. Maternal age, education level, and whether the child had ever visited a dentist were significant modifiers of subjective and objective caries assessments. Conclusions: From a clinical and dental public health perspective, our findings of a weak to moderate correlation of maternal assessments of their children’s caries experience may be concerning when reporting the burden of dental diseases in large population studies or for surveillance purposes that rely on self-reported measures and must therefore be utilized with caution because of the potential to result in underestimated disease burden.